The Evolution of Gene Expression in cis and trans. Issue 7 (July 2018) - Signor, Sarah A.; Nuzhdin, Sergey V.
Abstract : There is abundant variation in gene expression between individuals, populations, and species. The evolution of gene regulation and expression within and between species is thought to frequently contribute to adaptation. Yet considerable evidence suggests that the primary evolutionary force acting on variation in gene expression is stabilizing selection. We review here the results of recent studies characterizing the evolution of gene expression occurring in cis (via linked polymorphisms) or in trans (through diffusible products of other genes) and their contribution to adaptation and response to the environment. We review the evidence for buffering of variation in gene expression at the level of both transcription and translation, and the possible mechanisms for this buffering. Lastly, we summarize unresolved questions about the evolution of gene regulation. Highlights: cis -regulatory differences appear to be more commonly responsible for adaptive evolution, though there are exceptions that illustrate the importance of gene network context in the path by which evolution proceeds. Current evidence supports the supposition that genome-wide gene expression evolves under stabilizing selection. There is limited evidence that some of this stabilizing selection is due to compensatory cis–trans evolution, but more research is needed. Overall, when cis–trans contributions to gene expression differences are investigated there is an excess of compensatory cis–trans pairs. The observation of an excess of cis–trans pairs that are compensatory could be due to mutational and ascertainment bias, selection for compensatory mutations, buffering from gene-network feedback, or potentially communication between alleles (transvection).